Numerical study on aerodynamic resistance reduction of high-speed train using vortex generator - Li, Tian; Liang, Hao; Zhang, Jie; Zhang, Jiye (Engineering applications of computational fluid mechanics, 2023)
Vortex generator (VG) is one of the potential technical tools to reduce the aerodynamic resistance of high-speed trains. The passive control resistance reduction research of a high-speed train is carried out by using VG. Three typical installation locations, including flow separation point, boundary layer mutation and streamline transition location, and several nearby locations were selected to study the effect of VG location on the train aerodynamic characteristics. The results show that the tail car drag is significantly reduced when the VG is arranged at the boundary layer mutation, the tail car's resistance can be reduced by 15.42%. The tail car reduces resistance by 3.87% when VG is set at the flow separation point. By analyzing the flow field structure, we found that the VG arranged in front of the separation point triggers the flow separation, which destroys the balance between the separation and longitudinal vortex. It effectively reduces the strength of the separation vortex, thereby reducing the tail car's aerodynamic drag. The research provides a new thought for the aerodynamic resistance reduction of high-speed trains, and is of great significance to break the limitations of traditional aerodynamic drag reduction technology of trains.